Fungsi Manajemen di Padepokan Tari Langen Kusuma Kabupaten Ponorogo - rocky Dwi; Joko Winarko (Universitas Negeri Surabaya, 2026)
The Langen Kusuma Dance Padepokan in Ponorogo Regency is an arts institution that plays a role in preserving traditional dance. In practice, the management of the padepokan is inseparable from the implementation of management functions such as planning, organizing, implementing, evaluating, and developing. However, in its implementation, various obstacles are still encountered, such as limited resources, less than optimal management of practice time, and limited funding. Nevertheless, the padepokan remains active through various strategies and solutions implemented. This study aims to describe the management functions of the Langen Kusuma Dance Padepokan in Ponorogo Regency and identify the obstacles and solutions faced in its implementation. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included the founder of the padepokan, the head of the padepokan, and dance trainers, while the research object focused on the management system of the Langen Kusuma Dance Padepokan. The implementation of management functions including planning, organizing, implementing, evaluating, and developing has been running quite well at the Langen Kusuma Dance Padepokan. The division of work also supports management effectiveness. Despite resource, time, and funding constraints, efforts such as strengthening collaboration, increasing promotion, and optimizing resources have provided solutions. This has enabled the padepokan to remain viable and play an active role in preserving traditional dance arts. Keywords:management function, dance studio, Langen Kusuma Dance Padepokan.